A Study to Assess the Knowledge and Practice of Parents Regarding Home Management of Minor Ailments in Children Visiting Tertiary Care Hospital Mangaluru - K., Navitha; lobo, Melba Roshini; J., Umarani (Journal of Health and Allied Sciences NU, 2023)
Background The nation's future depends on its children. Minor illnesses are a common occurrence during childhood. It is crucial to evaluate parents' knowledge and practice when it comes to dealing with minor illnesses. This study aimed to assess the knowledge and practice of parents regarding home management of minor ailments in children.Methods The descriptive research design was adopted for this study. The sample consisted of 65 parents of under-5 children The sample was selected on the basis of the purposive sampling technique. Data was collected using a knowledge questionnaire and practice checklist related to the management of minor illnesses in children including fever, upper respiratory tract infection (URTI; cough, cold, sore throat), diarrhea, vomiting, abdominal colic, and superficial wound. Data collected from the subjects were analyzed by descriptive and inferential statistics.Results Study revealed that 80% had good knowledge, 20% had moderate knowledge, and none of them had poor knowledge on home management of minor ailments. In terms of practice, 55.4% of parents had moderate practice in the management of fever, 93.8% had good practice regarding the management of URTI, 43.1% had a good practice in managing diarrhea at home, 47.7% of parents had poor practice regarding home management of abdomen colic, 56.9% parents had a good practice on management of vomiting at home, and 92.3% had good practice score on managing superficial wounds at home. There was a significant association found with education status and knowledge score, as well as educational status and occupation with URTI practice and source of health information with fever at p-value less than 0.05 level of significance.Conclusion The results of this study showed that parents of under-5 children had good knowledge and practice regarding home management of minor ailments.
Keywords: knowledge; minor ailments; parents; under-5 children